Potential of Sugar Cane As an Alternative Raw Material for Making Activated Carbons - A.S. Dwi Saptati Nur Hidayati; Silva Kurniawan; Nalita Widya Restu; Bambang Ismuyanto (Natural B, Journal of Health and Environmental Sciences, 2016)
This research studied to utilize the bagasse to be used as activated karbon in particular for the adsorption of Ca2+. The manufacture of activated carbon consists of carbonization dan activation process. Temperature variation for carbonization process in this research are 500°C, 550°C, 600°C, 650°C and 700°C then proceed with the activation process by carbon reflux with 6 M H2SO4 for 4 hours. Carbonization yield will decrease with increasing temperature carbonization. While the ash content, surface area, pore volume, and adsorption capacity of Ca2+ will increase with increasing temperature of carbonization. Obtained activated carbon is best activated karbon made at a temperature of 700°C with an activation carbonization which has a surface area 100.62 m2/g, 22.3750 Å pore diameter, pore volume of 22.376 mL/g, can eliminate the Ca2+ up to 13.26 %.